2013
DOI: 10.19026/ajfst.5.3357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sorghum Flour Addition on Chemical and Rheological Properties of Hard White Winter Wheat

Abstract: This study was carried out to investigate the chemical and rheological properties of different blends prepared using hard white winter wheat (HWWW; Triticum aestivum Desf.) and whole or decorticated sorghum (Sorghum bicolor). Whole and decorticated sorghum were used to replace 5, 10, 15 and 20% of wheat flour. Wheat samples had higher protein, moisture and calcium values and lower fat, ash, carbohydrates, iron and phosphorous values compared to whole and decorticated sorghum flours. Decortication of sorghum gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 13 publications
4
19
0
Order By: Relevance
“…This implied that the extent of liquefaction and diastatic activity of the starches in the blends decreased as the proportion of rice flour increased (Schiller 1984, Watson 1984and Meera 2010. Abdelghafor et al (2013)stated that sorghum/ wheat flour blend showed wet dry gluten percentage decreased with increasing sorghum flour in the blend. Amir et al (2015) found that, flour blend contained 20% sorghum flour + 80% wheat flour possessed the highest percentage of protein (14.8%) and ash (1.79%).…”
Section: Role Of Pulse Flour Substitutionmentioning
confidence: 87%
“…This implied that the extent of liquefaction and diastatic activity of the starches in the blends decreased as the proportion of rice flour increased (Schiller 1984, Watson 1984and Meera 2010. Abdelghafor et al (2013)stated that sorghum/ wheat flour blend showed wet dry gluten percentage decreased with increasing sorghum flour in the blend. Amir et al (2015) found that, flour blend contained 20% sorghum flour + 80% wheat flour possessed the highest percentage of protein (14.8%) and ash (1.79%).…”
Section: Role Of Pulse Flour Substitutionmentioning
confidence: 87%
“…There is little agreement on wheat-sorghum dough development. While two studies concluded that the dough development time decreased [ 49 , 50 ] the more sorghum was added, other researchers found that dough development time increased with increasing sorghum addition to wheat [ 6 , 7 ]. Therefore, there is no solid evidence whether sorghum requires a longer kneading time for dough structure development.…”
Section: Physical Properties and Dough Rheology Of Wheat-sorghum Blendsmentioning
confidence: 99%
“…More consistent results within the farinograph studies could be seen with regard to dough stability. The more sorghum was added to wheat flour, the shorter was the stability of the doughs [ 5 , 7 , 19 , 49 , 50 ]. This leads to the assumption that sorghum addition to wheat dough is less stable against kneading than a 100% wheat flour dough.…”
Section: Physical Properties and Dough Rheology Of Wheat-sorghum Blendsmentioning
confidence: 99%
“…Corn grains and sorghum grains were cleaned from foreign materials and milled using laboratory mill (3100, Perten Instruments, Sweden) to obtained whole sorghum flour. Corn and Sorghum flour was packed in polyethylene bags and stored at (−18˚C) until used (Abdelghafor, et al, 2013).…”
Section: Preparation Of Flourmentioning
confidence: 99%